Optimasi Formulasi Sabun Pembersih Wajah Antibakteri Variasi Kombinasi Minyak Atsiri Kulit Jeruk dan Ekstrak Daun Kemangi: Optimization of Antibacterial Facial Cleansing Soap Formulation Variations Combinations of Orange Peel Essential Oil and Basil Leaf Extract - Sari, Gigih Kenanga; Hapsari, Estuningtyas Ayu (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
Orange peel essential oil and basil leaf extract are known as natural ingredients that contain medicinal ingredients. The extracts of these two plants are useful as antibacterials. The aims of this research are to determine the antibacterial activity of facial soap containing the active ingredients orange peel essential oil and basil leaf extract. The methods studied include organoleptic properties, pH value, foam height, free alkali content, specific gravity and antibacterial activity. The type of research used is experimental research. Data collection was carried out by measuring, while data analysis was descriptive and analytical. The research design used was a post-test only control design. Conclusions include the preparation of facial cleansing soap with a combination of orange peel essential oil and basil leaf extract which meets SNI requirements which is classified as an inhibitory bacterial work zone but the most optimal is F3, there are differences in the diameter of the inhibitory zone for the growth of Staphylococcus aureus bacteria in facial cleansing soap with a combination of active ingredients. orange peel essential oil and basil leaf extract. Keywords: facial cleansing soap, orange peel essential oil, basil leaf extract Abstrak Minyak atsiri kulit jeruk dan ekstrak daun kemangi dikenal sebagai bahan alami yang mengandung bahan obat. Ekstrak kedua tumbuhan ini bermanfaat sebagai antibakteri. Tujuan penelitian ini adalah untuk mengetahui aktivitas antibakteri sabun wajah yang mengandung bahan aktif minyak atsiri kulit jeruk dan ekstrak daun kemangi. Metode yang diteliti meliputi sifat organoleptik, nilai pH, tinggi busa, kandungan alkali bebas, berat jenis dan aktivitas antibakteri. Jenis penelitian yang digunakan adalah penelitian eksperimen. Pengumpulan data dilakukan dengan cara pengukuran, sedangkan analisis data bersifat deskriptif dan analitis. Desain penelitian yang digunakan adalah post test only control design. Sediaan sabun pembersih wajah dengan kombinasi minyak atsiri kulit jeruk dan ekstrak daun kemangi telah memenuhi syarat SNI yang tergolong zona kerja penghambat bakteri namun yang paling optimal adalah F3, terdapat perbedaan diameter zona hambat. untuk pertumbuhan bakteri Staphylococcus aureus pada sabun pembersih wajah dengan kombinasi bahan aktif. minyak esensial kulit jeruk dan ekstrak daun kemangi. Kata Kunci: sabun, pembersih, wajah, jeruk, kemangi